Representasi Stigmatisasi Obesitas: Analisis Semiotika Karakter Don dalam Film JUMBO dan Implikasinya terhadap Persepsi Tubuh Ideal - Reza Mehdi Fauzi; Zahrotul Munawwaroh; Mohammad Syarrafah (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This research analyzes the representation of obesity stigmatization through the character Don in the film "Jumbo" by Ryan Adriandhy using Roland Barthes' semiotic approach. Through denotative, connotative, and mythological analysis, the research reveals how the film constructs obesity as a visual and moral anomaly with implications for social perceptions of the ideal body. At the denotative level, Don's character is represented with cinematic techniques that emphasize his body proportions as a deviation from the norm.Connotatively, this representation activates associations between obesity and social incapacity and failure of self-control. At the mythological level, the film naturalizes the view that obesity is a consequence of misguided personal choices. Although there are moments of resistance that acknowledge Don's complexity as an individual, this resistance is limited and does not threaten the dominant structure that idealizes the slender body. The implications are significant for the construction of social perception and the development of body positivity discourse, where media plays a role in reinforcing stigma through a "semiotic circle" that perpetuates body-based discrimination. This research emphasizes the importance of representational transformation in media to build more inclusive perceptions of body diversity, with theoretical implications for media studies and practical implications for media policy, public education, and mental health advocacy.